2019
DOI: 10.1002/ajim.23079
|View full text |Cite
|
Sign up to set email alerts
|

Night shift work and cardiovascular disease biomarkers in female nurses

Abstract: Background: Night shift work is associated with cardiovascular disease, but its associations with cardiovascular disease biomarkers are unclear. We investigated these associations in a study of female nurses. Methods:We used data from the Nurses' Health Study II for total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides, C-reactive protein (CRP), and fibrinogen. The sample sizes for our analysis ranged from 458 (fibrinogen) to 3574 (total cholesterol).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…However, the NHS II (Nurses’ Health Study II) cohort showed no association between recent night shifts and CRP levels (CRP levels were non significantly higher among nurses who had worked rotating night shifts for more than one year compared to nurses who had never worked rotating night shifts). They only used one time-point of blood collection and determined with questionnaires the number of night shifts worked in the 2 weeks before the blood sampling, and total years of rotating night shift work ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the NHS II (Nurses’ Health Study II) cohort showed no association between recent night shifts and CRP levels (CRP levels were non significantly higher among nurses who had worked rotating night shifts for more than one year compared to nurses who had never worked rotating night shifts). They only used one time-point of blood collection and determined with questionnaires the number of night shifts worked in the 2 weeks before the blood sampling, and total years of rotating night shift work ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory settings, sleep deprivation has been associated with an increase in biomarkers of CVD risk and blood pressure 21–24 . Results in shift‐work settings are mixed, likely due to differences in shift‐work schedules and study designs 25–29 . However, in field settings, circadian misalignment and sleep deprivation co‐occur and show significant and clinically meaningful interindividual differences by chronotype 30–34 .…”
Section: Circadian Rhythms and Chronic Disease Riskmentioning
confidence: 99%
“…With the rapid economic growth of modern society, shift and night work is becoming increasingly widespread in various industries such as food production, entertainment, aviation, healthcare, and transportation ( 1 3 ). However, the disruption of circadian rhythms caused by shift and night work poses a significant challenge to public health, increasing the risk of cardiovascular disease, cancer, diabetes, and neuropsychiatric disorders ( 4 7 ), even causing specific mortality ( 8 ). Recent studies have shown that encountering conditions such as night shift work schedules can lead to lack of sleep, poor sleep quality, reduced recovery, and increased physical stress ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%